1985
DOI: 10.1126/science.3975629
|View full text |Cite
|
Sign up to set email alerts
|

Developmentally Controlled Expression of Immunoglobulin V H Genes

Abstract: Although antibody diversity arises mainly from apparently random combinatorial and somatic mutational mechanisms acting upon a limited number of germline antibody genes, the antibody repertoire develops in an ordered fashion during mammalian ontogeny. A series of early pre-B and B-lymphocyte cell lines were examined to determine whether an ordered rearrangement of gene families of the variable region of immunoglobulin heavy chains (VH) may be the basis for the programmed development of the antibody response. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
180
3
1

Year Published

1989
1989
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 348 publications
(195 citation statements)
references
References 49 publications
11
180
3
1
Order By: Relevance
“…Previous reports have indicated that restrictions in Ag specificities are achieved by limited and preferential usage of certain V H and V gene segments (12,28). Preferential gene use reflected the proximity of gene segments in chromosomal position (8,9,12). Fetal diversity was also reported to reflect limited diversification of the CDR3 region during early ontogeny.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous reports have indicated that restrictions in Ag specificities are achieved by limited and preferential usage of certain V H and V gene segments (12,28). Preferential gene use reflected the proximity of gene segments in chromosomal position (8,9,12). Fetal diversity was also reported to reflect limited diversification of the CDR3 region during early ontogeny.…”
Section: Discussionmentioning
confidence: 97%
“…The finding that the two most distal V genes were not detected in the fetal nonproductive repertoire suggests that, as in the mouse, proximity of gene segments in the chromosome position plays a role in preferential V J rearrangements early in human ontogeny. However, it is different in that this positional effect is not as profound as in mouse (8,9,36), because rearrangement of V genes in the human fetus occurred throughout the entire V locus, except the most distal two genes. These findings indicate that nonrandom gene segment use largely reflects a regulatory process that is intrinsic to the specific gene element and is independent of the stage of B cell maturation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By analogy with studies of VDJ H recombination in immature B cells, one of the most obvious possibilities would be the relative proximity of a given V␤ segment to the DJ␤ cluster. Indeed, in both fetal and adult mouse pre-B cells, it has been shown that DJ H -proximal V H segments (such as V H 81X) are preferentially rearranged (37)(38)(39)(40)(42)(43)(44). In marked contrast to pre-B cells, the most DJ␤-proximal V␤ segments in DN3 thymocytes (V␤7 and V␤3) are apparently rearranged at relatively low frequency, whereas the relatively distal V␤8.2 segment is rearranged most frequently.…”
Section: Possible Origin Of Biased Vdj␤ Recombination In Immature T Cmentioning
confidence: 97%
“…At the IgH locus, there is a large body of evidence indicating that proximal V H segments rearrange preferentially to DJ H segments during ontogeny (37)(38)(39)(40)(41)(42)(43)(44). Thus it is possible that the variations observed in V␤ usage among DN3 thymocytes reflect proximity to the DJ␤ segments.…”
Section: Biased V␤ Repertoire In Dn3 Thymocytes Is Independent Of Promentioning
confidence: 99%